Clinicopathological and bacteriological studies on lamb bacterial enteritis and monitoring the oregano oil and vitamins A,D3,E effect on its treatment - Darwish, Asmaa Abdallah; Fawzy, Marwa; Osman, Wafaa Abd Latif; Ebissy, Eman A El (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The objective of the study was to assess the effect of A,D3,E (I/M) and oregano oil extract 15% on some clinicopathological parameters during lamb bacterial enteritis treatment. Materials and Methods: Sixty Barki lambs, 20 apparently healthy (control group) and, 40 suffered from bacterial enteritis [enteric group (EG)], were subdivided into four treated groups (TGs): antibiotic group (AG), antibiotic + A,D3,E group (A + A,D3,E), antibiotic + oregano oil (AOG), and oregano group (OG). Fecal swabs were collected from EG then aseptically cultured, isolated, phenotypically identified, genotypically confirmed, and sequenced by PCR 16srRNA. Paper disk diffusion test was used for estimation of oregano oil extract 15% antibacterial activity. After blood sample aspiration from all animals, they were clinicopathologically and statistically analyzed. Results: Escherichia coli, followed by Salmonella species and then Klebsiella species, was the main causative agents of lamb diarrhea and were susceptible to oregano oil extract 15%. A + A,D3,E and AOG showed significant (p < 0.05) enhancement of some clinicopathological parameters more than AG or OG. Matrix metalloproteinases (MMP-2 and MMP-9) and total antioxidant capacity (TAC), yielded area under the curve, sensitivity, negative predictive value as 1, 100% and 100% respectively, were determined in both EG and TGs. Conclusion: Oregano oil extract 15% has good antibacterial properties against enteric bacteria in vitro and in vivo. The combination between antibiotic and antioxidant vitamins or oregano plant extract of 15% has a good impact on some clinicopathological alterations in lamb bacterial enteritis treatment. TAC, MMP-9, and MMP-2 may be good markers for the disease and its treatment follow-up. J. Adv. Vet. Anim. Res., 8(2): 291-299, June 2021